#### Answer

$18 + 12i$

#### Work Step by Step

$6i(2 - 3i) = 12i - 18i^2 = 12i - 18(-1) = 12i + 18 = 18 + 12i$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$18 + 12i$

$6i(2 - 3i) = 12i - 18i^2 = 12i - 18(-1) = 12i + 18 = 18 + 12i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.